Positive pole piece as well as preparation method and application thereof

By using lithium iron phosphate particles of different particle sizes in the positive electrode sheet for particle grading, the problem of reduced number of slopes and fast cycle attenuation in the early stage of normal temperature cycle is solved, and a longer cycle life and better low-temperature discharge capacity are achieved.

CN119695065APending Publication Date: 2025-03-25ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411891191.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing high-power lithium iron phosphate positive electrode materials have reduced the number of slopes and fast cycle attenuation in the early stage of the normal temperature cycle.

Method used

The active material layer including lithium iron phosphate particles of different particle sizes is adopted to improve compaction density and lithium ion diffusion efficiency through particle grading, extend the number of early climbing circles and slow down cycle attenuation.

Benefits of technology

The cycle life and low-temperature discharge capacity of the positive electrode plate are improved, the number of climbing circles in the early stage is extended, and the cycle attenuation speed is slowed down.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005200701960000151
    Figure BDA0005200701960000151
  • Figure BDA0005200701960000152
    Figure BDA0005200701960000152
  • Figure BDA0005200701960000153
    Figure BDA0005200701960000153
Patent Text Reader

Abstract

The invention belongs to the technical field of pole piece preparation, and particularly relates to a positive pole piece and a preparation method and application thereof. The positive pole piece comprises a current collector and an active material layer arranged on at least one surface of the current collector; the active substance layer comprises an active substance; the active substance comprises lithium iron phosphate, and the lithium iron phosphate comprises first particles with the particle size of d1, second particles with the particle size of d2 and third particles with the particle size of d3; wherein d1 is less than 200nm, d2 is more than or equal to 200nm and less than or equal to 800nm, and d3 is more than 800nm. The lithium iron phosphate comprises three kinds of lithium iron phosphate particles with different particle sizes, and by adopting particle grading, compaction can be improved, the number of climbing turns in the early stage can be prolonged, the cycle life can be prolonged, too fast cycle attenuation can be slowed down, and the low-temperature discharge capacity and cycle performance of the battery cell can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of electrode preparation, and specifically relates to a positive electrode electrode and a preparation method and application thereof. Background Art

[0002] Lithium iron phosphate LiFePO4 stands out in the lithium-ion battery cathode material due to its advantages such as low price, long cycle and environmental friendliness, and has attracted much attention in lithium-ion battery electric vehicles in recent years. With the market's demand for energy density, high-density lithium iron phosphate materials and high-power lithium iron phosphate materials have become the main research directions. However, high-density lithium iron phosphate materials will cause the battery to lose a certain rate and low-temperature performance. High-power lithium iron phosphate materials can improve the low-temperature performance of the battery, but they have many side reactions at the electrolyte interface, lithium ion loss, reduced number of climbing laps in the early stage of normal temperature cycling, and fast cycle attenuation. Summary of the invention

[0003] Therefore, the technical problem to be solved by the present application is to overcome the defects of the prior art positive electrode materials such as the reduced number of early climbing cycles in room temperature cycles and the fast cycle attenuation rate, thereby providing a positive electrode plate and its preparation method and application.

[0004] To this end, this application provides the following technical solutions.

[0005] In the first aspect, the present application provides a positive electrode plate, which includes a current collector and an active material layer arranged on at least one surface of the current collector; the active material layer includes an active material; the active material includes lithium iron phosphate, and the lithium iron phosphate includes first particles with a particle size of d1, second particles with a particle size of d2, and third particles with a particle size of d3; wherein d1 is less than 200nm, 200nm≤d2≤800nm, and d3 is greater than 800nm.

[0006] Furthermore, d1≥50nm; and / or, d3≤1500nm; and / or, the lithium iron phosphate further includes fourth particles with a particle size of d4, d4≥2μm.

[0007] Further, within an area of ​​50 μm×50 μm on the surface of the active material layer, based on the total number of all lithium iron phosphate particles, the number of the first particles accounts for 35%-40%; and / or,

[0008] The amount of the second particles accounts for 60%-64%; and / or,

[0009] The amount of the third particles accounts for 0.5%-1%; and / or,

[0010] The quantity of the fourth particles accounts for less than 0.1%.

[0011] Furthermore, the first particles, the second particles and the third particles are primary particles, and the fourth particles are secondary particles agglomerated from the first particles.

[0012] Furthermore, the active material includes a lithium supplement; the lithium supplement includes at least one of a ternary lithium compound and a binary lithium compound.

[0013] Furthermore, the mass ratio a of the first particles to the lithium supplement agent satisfies 1≤a≤10;

[0014] And / or, the ternary lithium compound is Li5FeO4.

[0015] Furthermore, the raw material of lithium iron phosphate in the active material includes a first lithium iron phosphate and a second lithium iron phosphate; the first particles come from the first lithium iron phosphate, and the second particles and the third particles come from the second lithium iron phosphate.

[0016] Further, based on the total mass of the active material, the mass content W1 of the first lithium iron phosphate satisfies: 0<W1<40wt%; the mass content W2 of the second lithium iron phosphate satisfies: 60wt%≤W2<100wt%, and the mass content W3 of the lithium supplement agent satisfies: W3<5wt%; and / or,

[0017] The particle size distribution curve of the first lithium iron phosphate is a bimodal curve, the high peak particle size of the bimodal curve is the first peak particle size, and the low peak particle size is the second peak particle size; the first peak particle size is higher than 10 μm, and the second peak particle size is not higher than 1 μm; and / or,

[0018] The particle size distribution curve of the second lithium iron phosphate is a bimodal curve, the high peak particle size of the bimodal curve is the third peak particle size, and the low peak is the fourth peak particle size; the third peak particle size is not higher than 1 μm, and the fourth peak particle size is 1 μm-10 μm.

[0019] Furthermore, the mass content of the active material in the active material layer is 85-98wt%; and / or,

[0020] The surface density of the positive electrode sheet is 15-28 mg / cm 2 and / or,

[0021] The compaction density of the positive electrode sheet is 2.0-2.7 g / cm 3 and / or,

[0022] The surface resistance of the positive electrode plate is 200-500 mΩ; and / or,

[0023] The thickness of the positive electrode plate is 120-205 μm.

[0024] In a second aspect, the present application provides a battery comprising the above-mentioned positive electrode plate.

[0025] The technical solution of this application has the following advantages:

[0026] 1. The positive electrode plate provided in the present application comprises a current collector and an active material layer disposed on at least one surface of the current collector; the active material layer comprises an active material; the active material comprises lithium iron phosphate, and the lithium iron phosphate comprises a first particle with a particle size of d1, a second particle with a particle size of d2, and a third particle with a particle size of d3; wherein d1 is less than 200nm, 200nm≤d2≤800nm, and d3 is greater than 800nm. The lithium iron phosphate comprises lithium iron phosphate particles of three different particle sizes, and the use of particle grading can improve compaction, extend the number of early climbing laps, improve cycle life, slow down excessive cycle attenuation, and improve the low-temperature discharge capability and cycle performance of the battery cell. DETAILED DESCRIPTION

[0027] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.

[0028] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0029] High-density lithium iron phosphate is usually used in the positive electrode plate of the prior art, but it will cause the battery to lose a certain degree of low-temperature performance. High-power lithium iron phosphate can improve the low-temperature performance of the battery, but it has problems such as reduced number of climbing laps in the early stage of the cycle and too fast cycle decay. In order to solve the problems of the prior art, this application provides the following technical solutions.

[0030] In a first aspect, the present application provides a positive electrode plate, which includes a current collector and an active material layer arranged on at least one surface of the current collector; the active material layer includes an active material, and the active material includes lithium iron phosphate, and the lithium iron phosphate includes first particles with a particle size of d1, second particles with a particle size of d2, and third particles with a particle size of d3; wherein d1 is less than 200nm, 200nm≤d2≤800nm, and d3 is greater than 800nm.

[0031] The active material in the positive electrode plate of the present application includes lithium iron phosphate of different particle sizes, wherein the first particle with a particle size of d1 comes from high-power lithium iron phosphate, the second particle with a particle size of d2 and the third particle with a particle size of d3 come from high-compacted lithium iron phosphate. High-power lithium iron phosphate can reduce the surface resistance of the electrode plate and the ohmic internal resistance of the battery cell, and weaken the internal polarization; the particle size d1 of the first particle is less than 200nm, and the smaller particle size shortens the diffusion path of lithium ions, accelerates the diffusion of lithium ions, and improves the low-temperature discharge capability. The particle size d1 of the first particle of the present application is less than 200nm, the particle size d2 of the second particle is 200nm-800nm, and the particle size d3 of the third particle is greater than 800nm. The particle grading between these particles can improve compaction, make the contact between particles closer, accelerate the charge transfer rate, reduce the internal resistance of the battery, reduce polarization, improve the dynamic performance, and reduce the loss of lithium ions during the cycle. The particle sizes of the first, second and third particles are appropriate, the activation levels of different particles are slightly different, relatively more lithium ions are released, and relatively more lithium reaches the negative electrode. In the early cycle process, the lithium stored in the negative electrode will continue to be embedded back into the positive electrode, and the lithium that can be released from the positive electrode side will continue to increase, extending the early climbing, improving the cycle life, and slowing down the rapid cycle decay. The particle grading of this application takes advantage of the different particle sizes. Large particles can provide higher mechanical strength, which is helpful for the stability and consistency of the electrode structure; small particles can fill the gaps in large particles, further improve the compaction density of the material, shorten the lithium ion diffusion path, accelerate the diffusion of lithium ions, improve the capacity retention rate, reduce the changes in the electrode structure, and improve the low-temperature discharge capacity and cycle performance of the battery cell.

[0032] As an example, the particle size d1 of the first particle is 10nm, 30nm, 50nm, 80nm, 110nm, 140nm, 170nm, 200nm or within the range of any two of the above values. The particle size d2 of the second particle is 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm ​​or within the range of any two of the above values. The particle size d3 of the third particle is 800nm, 1000nm, 1200nm, 1400nm, 1600nm, 1800nm, 2000nm or within the range of any two of the above values. It should be explained that the particle size of the lithium iron phosphate particles is obtained by testing using a method known in the art, and d1, d2, and d3 are all average particle sizes of lithium iron phosphate particles. For example, a scanning electron microscope is used to obtain a SEM image of lithium iron phosphate particles, and the particle sizes of 100 particles within the corresponding particle size range are tested respectively, and the average value is taken to obtain d1, d2, and d3.

[0033] In an optional embodiment, d1≥50nm; and / or, d3≤1500nm; and / or,

[0034] The lithium iron phosphate further includes a fourth particle with a particle size of d4, d4 ≥ 2 μm, and it should be noted that d4 is the average particle size of the fourth particle, and d4 is obtained by testing using a method known in the art. For example, a SEM image of the lithium iron phosphate particles is obtained using a scanning electron microscope, and the particle sizes of 100 particles within the corresponding particle size range are tested, and the average value is taken to obtain d4.

[0035] The present application regulates the first particle size d1 ≥ 50nm and the third particle size d3 ≤ 1500nm, which can better achieve particle grading, make the contact between particles closer, accelerate lithium ion diffusion, extend the early climbing, and slow down attenuation. The first particle d1 ≥ 50nm helps to reduce lithium ion loss and side reactions at the interface between active substances and electrolytes, and improve battery cycle performance. The third particle size d3 ≤ 1500nm helps to reduce particle breakage in the late cycle, which affects battery cycle performance and slows down rapid cycle attenuation. The fourth particle d4 ≥ 2μm helps to improve slurry stability, improve processing performance, and achieve better dispersion of active substances, conductive agents and binders, reduce the surface resistance of the pole sheet, and reduce internal polarization, which helps to improve cycle performance, slow down cycle attenuation, and improve battery cell performance.

[0036] In an optional embodiment, within an area of ​​50 μm×50 μm on the surface of the active material layer, based on the total number of all lithium iron phosphate particles, the number of the first particles accounts for 35%-40%; and / or,

[0037] The amount of the second particles accounts for 60%-64%; and / or,

[0038] The amount of the third particles accounts for 0.5%-1%; and / or,

[0039] The quantity of the fourth particles accounts for less than 0.1%.

[0040] The present application regulates the number ratio of different particle sizes of lithium iron phosphate in the active material, so that the active material has a suitable specific surface area, further reduces side reactions and improves the cycle life. The present application regulates the number ratio of different particle sizes and also helps to shorten the lithium ion diffusion path and increase battery dynamics, such as rate performance and low-temperature discharge capability; controlling the number of small-size particles helps to improve the slurry stability and ensure the slurry content, improve the consistency of the pole piece coating, and thus help to reduce the internal resistance of the battery and improve the electrical performance. If the large particles account for too much, cracks are easily generated during the cycle, new interfaces are formed, side reactions occur, and the cycle and life are reduced. It should be noted that the number ratio of particles of each particle size of lithium iron phosphate is obtained by testing according to methods known in the art. Here is a method in which the active material layer is used as a sample, a scanning electron microscope is used to obtain a sample SEM image, and an area of ​​50μm×50μm is used as the unit area. The number of the first particle, the second particle, the third particle and the fourth particle is counted, and the number ratio is calculated; different positions of the active material layer are taken, repeated 10 times, and the average value is used as the number ratio of particles of different particle sizes.

[0041] As an example, the amount of the first particles accounts for 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt% or is within the range formed by any two of the above values. The amount of the second particles accounts for 60wt%, 61wt%, 62wt%, 63wt%, 64wt% or is within the range formed by any two of the above values. The amount of the third particles accounts for 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt% or is within the range formed by any two of the above values.

[0042] In an optional embodiment, the first particles, the second particles and the third particles are primary particles, and the fourth particles are secondary particles agglomerated from the first particles. It should be noted that the fourth particles are secondary particles agglomerated from the first particles, and may be broken up during the batching stage, so the number of the fourth particles accounts for less than 0.1%, including the case where there is no fourth particle, that is, the number of the fourth particles accounts for 0. The primary particles and the secondary particles can be observed through a microscope test.

[0043] In an optional embodiment, the active material includes a lithium supplement; the lithium supplement includes at least one of a ternary lithium compound and a binary lithium compound. The present application adds a lithium supplement to the active material layer, and the lithium supplement can replenish the lithium ions lost during the first cycle, and slowly releases it during the cycle to ensure long-term and stable lithium loss compensation, further extend the initial ramp, increase the number of ramps, prevent the cycle from decaying too fast, improve the capacity retention rate and cycle life, reduce the structural changes of the electrode material, and further improve the cycle performance of the battery. The lithium supplement also has a synergistic effect with the first particle (i.e., high-power lithium iron phosphate). On the one hand, the lithium supplement forms a denser SEI film on the negative electrode side through lithium removal in the formation stage, reducing the DCR internal resistance of the system; on the other hand, the addition of high-power small particles shortens the lithium ion diffusion path. In summary, the appropriate addition of lithium supplements and first particles can further improve the low-temperature discharge capability and cycle performance of the battery cell.

[0044] Further, in the ternary lithium compound LixMO4, M is at least one element selected from Fe, Co, Mn and Ni; the ternary lithium compound is a lithium salt composed of lithium oxide and transition metal oxide, including at least one of Li2NiO2, Li5FeO4, Li6CoO4, Li2MoO3 and Li8ZrO6, and x and y vary according to M and are the molar ratios of the elements. The binary lithium compound is at least one selected from Li2O, Li2O2, LiF, Li2S, Li3N and Li2Se.

[0045] In an optional embodiment, the mass ratio a of the first particles to the lithium supplement agent satisfies 1≤a≤10;

[0046] And / or, the ternary lithium compound is Li5FeO4.

[0047] In an optional embodiment, the raw material of lithium iron phosphate in the active material includes a first lithium iron phosphate and a second lithium iron phosphate; the first lithium iron phosphate is a high-power lithium iron phosphate; and the second lithium iron phosphate is a high-density lithium iron phosphate.

[0048] In an optional embodiment, based on the total mass of the active material, the mass content W1 of the first lithium iron phosphate satisfies: 0<W1<40wt%; the mass content W2 of the second lithium iron phosphate satisfies: 60wt%≤W2<100wt%; the mass content W3 of the lithium supplement agent satisfies: W3<5wt%; and / or,

[0049] The particle size distribution curve of the first lithium iron phosphate is a bimodal curve, the high peak particle size of the bimodal curve is the first peak particle size, and the low peak particle size is the second peak particle size; the first peak particle size is higher than 10 μm, and the second peak particle size is not higher than 1 μm; and / or,

[0050] The particle size distribution curve of the second lithium iron phosphate is a bimodal curve, the high peak particle size of the bimodal curve is the third peak particle size, and the low peak is the fourth peak particle size; the third peak particle size is lower than 1 μm, and the fourth peak particle size is 1 μm-10 μm.

[0051] The present application regulates the amount of the first lithium iron phosphate, the second lithium iron phosphate and the lithium supplement to further improve the low temperature cycle performance of the battery. It should be explained that the high peak value is the higher peak in the bimodal curve, and the low peak value is the lower peak in the bimodal curve. The particle size distribution curve is obtained by testing and instrumentation using methods known in the art, and the peak particle size is obtained by the particle size distribution curve. Here is one example, Malvern, Master Size 3000.

[0052] As an example, W1 is 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt% or in the range of any two of the above values. W2 is 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt% or in the range of any two of the above values. W3 is 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt% or in the range of any two of the above values.

[0053] In an optional embodiment, the mass content of the active substance in the active substance layer is 85-98wt%; and / or,

[0054] The surface density of the positive electrode sheet is 15-28 mg / cm 2 and / or,

[0055] The compaction density of the positive electrode sheet is 2.0-2.7 g / cm 3 and / or,

[0056] The surface resistance of the positive electrode plate is 200-500 mΩ; and / or,

[0057] The thickness of the positive electrode plate is 120-205 μm.

[0058] It is understandable that the surface resistance, surface density and thickness of the positive electrode sheet affect each other. The surface density is 15-28 mg / cm 2 , compacted density is 2.0-2.7g / cm 3, a thickness of 120-205μm can reduce polarization, prevent the battery's internal resistance from being too high, and ensure lithium ion transmission and battery capacity.

[0059] As an example, the mass content of the active material in the active material layer is 85wt%, 86wt%, 87wt%, 88wt%, 89wt%, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98% or within the range of any two of the above values. The surface density of the positive electrode sheet is 15mg / cm 2 、16mg / cm 2 、18mg / cm 2 , 20mg / cm 2 , 22mg / cm 2 , 24mg / cm 2 , 26mg / cm 2 、28mg / cm 2 Or within the range formed by any two of the above values. The surface resistance of the positive electrode sheet is 200mΩ, 250mΩ, 300mΩ, 350mΩ, 400mΩ, 450mΩ, 500mΩ or within the range formed by any two of the above values. The thickness of the positive electrode sheet is 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm, 200μm, 205μm or within the range formed by any two of the above values. The compacted density of the positive electrode sheet is 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 , 2.6g / cm 3 , 2.65g / cm 3 , 2.7g / cm 3 Or within the range formed by any two of the above values.

[0060] In an optional embodiment, the current collector comprises aluminum foil; and / or,

[0061] The current collector has a thickness of 8-16 μm.

[0062] In an optional embodiment, in the XRD spectrum of the positive electrode sheet, the peaks located at 2θ=17-18°, 20-21°, 22-23°, 25-26°, 29-30°, 32-33°, 35-36°, and 36-37° correspond to (200), (101), (210), (111), (211), (301), (311), and (121) of the lithium iron phosphate material, respectively; the peaks located at 2θ=16-17°, 21-22°, and 23-24° correspond to (111), (210), and (121) of the lithium supplement agent, respectively.

[0063] In an optional embodiment, the active material layer further includes an auxiliary agent; the auxiliary agent is selected from conventional auxiliary agents in the art, such as a conductive agent and a binder. Specifically, the conductive agent is selected from conventional conductive agents in the art, and the conductive agent includes at least one of conductive carbon black, acetylene black, conductive graphite, carbon nanotubes and carbon fibers. The binder is selected from conventional conductive agents in the art, and the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, polyacrylic acid and carboxymethyl cellulose.

[0064] In an optional embodiment, the amount of the conductive agent and the binder is selected from the amounts known in the art. The mass content of the conductive agent in the active material layer is 1-5wt%; the mass content of the binder in the active material layer is 1-5wt%.

[0065] In a second aspect, the present application provides a method for preparing a positive electrode sheet, comprising: preparing an active material slurry; coating the active material slurry on at least one surface of a current collector to obtain a positive electrode sheet;

[0066] The active material slurry comprises the following steps:

[0067] (1) mixing the first lithium iron phosphate raw material and part of the second lithium iron phosphate raw material;

[0068] (2) Add the remaining second lithium iron phosphate raw material to the material obtained in step (1).

[0069] In an optional embodiment, before adding the remaining second lithium iron phosphate raw material, a step of adding an auxiliary agent is further included.

[0070] In an optional embodiment, the step of adding a lithium supplement agent is also included while adding the remaining second lithium iron phosphate raw material.

[0071] In an optional embodiment, after adding the remaining second lithium iron phosphate raw material, a step of adding a solvent is also included. It is understood that the solvent is added to the material according to a method known in the art, such as adding the solvent in multiple steps or adding it all at once. The solvent is selected from conventional solvents in the art, and the solvent includes NMP and the like.

[0072] In an optional embodiment, the active material slurry has a solid content of 50-59% and a viscosity of 3000-9000 mPa.s.

[0073] In a third aspect, the present application provides a battery. The battery is prepared according to a method known in the art.

[0074] It is understandable that the preparation of the battery also includes a formation process, which is carried out according to methods known in the art; the methods of the formation process include: hot pressing at room temperature 25°C, hot pressing aging at 45°C, or cold pressing at 25°C. Among them, the charging system of hot pressing at room temperature 25°C is: gradually increase the current to charge to 3.65V, then reduce the current to charge, and the cut-off voltage is 4.05V. It is understandable that if the battery cell produces gas at the end of formation, it needs to be cut and exhausted immediately, and the negative pressure of the cut exhaust is -75 to -85KPa, and the time is 10 to 15s.

[0075] The battery provided in this application has good low-temperature discharge capability and cycle performance.

[0076] In an optional embodiment, the battery further includes a negative electrode sheet; the negative electrode sheet is selected from conventional negative electrode sheets in the art. Specifically, the negative electrode sheet includes a current collector and a negative electrode active material layer disposed on at least one surface of the current collector; the active material in the negative electrode active material layer includes graphite, etc. The negative electrode active material layer also includes conventional additives, the additives including at least one of a conductive agent, a thickener, and a binder.

[0077] In an optional embodiment, the battery further comprises an electrolyte; the electrolyte is selected from conventional electrolytes in the art. As an example, the electrolyte comprises at least one of ethylene carbonate, propylene carbonate and diethyl carbonate.

[0078] In an optional embodiment, the battery further includes a diaphragm, which is disposed between the positive electrode plate and the negative electrode plate, and the diaphragm is selected from conventional diaphragms in the art. The material of the diaphragm includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polyphenylene sulfide, polyimide, polystyrene, polytetrafluoroethylene, polymethyl methacrylate, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, cellulose, etc.

[0079] Example 1

[0080] This embodiment provides a positive electrode sheet, including:

[0081] The current collector is an aluminum foil with a thickness of 12 μm;

[0082] The active material layer is arranged on both surfaces of the current collector; the active material layer includes an active material, a conductive agent carbon black and a binder polytetrafluoroethylene in a mass ratio of 96.4:1.6:2; the active material includes a first lithium iron phosphate LiFePO4, a second lithium iron phosphate LiFePO4 and a lithium supplement Li5FeO4 in a mass ratio of 8:90:2. The first lithium iron phosphate is a high-power lithium iron phosphate, and the second lithium iron phosphate is a high-density lithium iron phosphate; the lithium iron phosphate includes a first particle with a particle size of d1, a second particle with a particle size of d2, a third particle with a particle size of d3 and a fourth particle with a particle size of d4, the first particle and the fourth particle are from the high-power lithium iron phosphate, and the second particle and the third particle are from the high-density lithium iron phosphate; d1 is 100nm, d2 is 200nm, d3 is 900nm, d4 is 3μm, and the number of these four particles accounts for 36.25wt%, 63.05wt%, 0.65wt%, and 0.05wt% respectively.

[0083] This embodiment also provides a method for preparing the above-mentioned positive electrode sheet, comprising the following steps:

[0084] (1) Mix half of the high-density lithium iron phosphate with all of the high-power lithium iron phosphate and stir for 45 minutes.

[0085] (2) adding a conductive agent and a binder to the material obtained in step (1) and stirring;

[0086] (3) Add the remaining high-density lithium iron phosphate and lithium supplement to the material obtained in step (2), stir and mix, then add solvent NMP to obtain a slurry; the slurry has a solid content of 57.50% and a viscosity of 6500 mPa.s.

[0087] (4) Coating the slurry on both sides of the current collector, drying, and rolling to obtain a positive electrode sheet; wherein the coating single surface density is 16 mg / cm 2 The thickness of the pole piece after rolling is 0.127mm and the compaction density is 2.6g / cm 3 , the surface resistance is 220mΩ.

[0088] Example 2-23

[0089] This embodiment provides a positive electrode plate, which is basically the same as that of Embodiment 1, and the differences are shown in Table 1-2.

[0090] Comparative Example 1

[0091] This comparative example provides a positive electrode plate, which is basically the same as Example 1, except that it does not contain the first lithium iron phosphate and the lithium supplement agent. Other parameters are shown in Table 1-2.

[0092] Comparative Example 2

[0093] This comparative example provides a positive electrode sheet, which is basically the same as Example 1, except that the active material does not contain second particles. Other parameters are shown in Table 1-2.

[0094] Comparative Example 3

[0095] This comparative example provides a positive electrode sheet, which is basically the same as Example 1, except that the active material does not contain second particles. Other parameters are shown in Table 1-2.

[0096] Comparative Example 4

[0097] This comparative example provides a positive electrode sheet, which is basically the same as Example 1, except that the active material does not contain third particles. Other parameters are shown in Table 1-2.

[0098] Comparative Example 5

[0099] This comparative example provides a positive electrode sheet, which is basically the same as Example 1, except that the active material does not contain the first particles. Other parameters are shown in Table 1-2.

[0100] Preparation Example

[0101] This preparation example provides a battery, the battery comprising:

[0102] Positive electrode sheets are from various embodiments and comparative examples.

[0103] Negative electrode sheet: The negative electrode active material graphite, the thickener sodium carboxymethyl cellulose (CMC-Na), the binder styrene-butadiene rubber, and the conductive agent acetylene black are mixed in a weight ratio of 96.5:0.8:1.7:1, and deionized water is added to obtain the negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry is evenly coated on a copper foil with a thickness of 6 μm; the copper foil is dried at room temperature and then transferred to an oven at 80°C for drying for 10 hours, and then cold pressed and cut to obtain the negative electrode sheet.

[0104] Electrolyte: In a glove box filled with argon and with qualified water and oxygen content, ethylene carbonate, propylene carbonate and diethyl carbonate are mixed in a mass ratio of 1:1:1, and then fully dried lithium hexafluorophosphate (LiPF6) is quickly added and stirred evenly. After passing the moisture and free acid tests, an electrolyte is obtained; the content of LiPF6 in the electrolyte is 14wt%.

[0105] Diaphragm: comprising a base film (PE) with a thickness of 9 μm, one side of the base film is coated with a ceramic layer with a thickness of 2 μm, and the other side is coated with a rubber layer with a thickness of 2 μm; the ceramic layer material comprises boehmite, and the rubber layer material comprises PVDF.

[0106] Preparation of lithium-ion batteries: stack the positive electrode sheet, separator and negative electrode sheet in order, ensure that the separator is between the positive and negative electrode sheets to play an isolating role, and then obtain the bare battery cell without liquid injection by winding; place the bare battery cell in the outer packaging foil, inject the prepared electrolyte into the dried bare battery cell, and obtain the required lithium-ion battery after vacuum packaging, standing, forming, shaping and sorting processes.

[0107] Test Case

[0108] This test case provides performance tests for electrodes and batteries, as follows:

[0109] The test method of electrode surface resistance: Use electrode resistance meter to test the electrode surface resistance.

[0110] The test method of capacity retention rate is as follows: ①Stand at 25±2℃ for 30min; ②Discharge at 0.5C to the lower limit voltage; ③Stand at 30min; ④Charge at 1C to the upper limit voltage, with a cutoff current of 0.05C; ⑤Stand at 4H; ⑥Stand at different temperatures in a constant temperature box for 4H, then discharge at 1C to the lower limit voltage, and record the capacity. ⑦Stand at 25±2℃ for 4H; Repeat steps ④-⑦ until all temperature discharge tests are completed. The discharge temperatures are 25℃ and -20℃, respectively. The percentage ratio of the discharge capacity at -20℃ to 25℃ is recorded as T, and this ratio is used to characterize the battery capacity retention performance. The results are shown in Table 3.

[0111] Normal temperature cycle performance test method: Place the battery in a (25±3)℃ environment and let it stand for 3h. When the battery cell reaches (25±3)℃, charge the battery to 3.65V at 1C, and then discharge it to 2.2V at 1C. Record the initial capacity Q0. When the cycle reaches 800 times, use the previous discharge capacity as the battery capacity Q1, and calculate the 800-cycle capacity retention rate E OL (%). The number of cycles corresponding to the highest capacity retention rate in the ramp-up phase is recorded as C1. The results are shown in Table 3.

[0112]

[0113] Table 1 Parameters in each embodiment and comparative example

[0114]

[0115] Note: "0" in Table 1 means that the substance is not contained.

[0116] Table 2 Parameters in each embodiment and comparative example

[0117]

[0118]

[0119] Note: “ / ” in Table 2 means that the substance is not contained.

[0120] Table 3 Battery performance test results

[0121]

[0122]

[0123] According to the above test results, the active material of the present application includes lithium iron phosphate with particle grading, which can prolong the initial climbing, increase the number of climbing laps, improve the capacity retention rate, have good low-temperature charging and discharging capabilities, and slow down the cycle decay. Combined with the results in Table 1, the higher T value indicates that the battery of the present application has good low-temperature charging and discharging capabilities, the higher C1 indicates that the number of climbing laps is increased, and the higher E OL Higher values ​​indicate better cycle performance.

[0124] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection created by this application.

Claims

1. A positive electrode sheet, characterized in that: The positive electrode plate includes a current collector and an active material layer arranged on at least one surface of the current collector; the active material layer includes an active material; the active material includes lithium iron phosphate, and the lithium iron phosphate includes first particles with a particle size of d1, second particles with a particle size of d2, and third particles with a particle size of d3; wherein d1 is less than 200nm, 200nm≤d2≤800nm, and d3 is greater than 800nm.

2. The positive electrode sheet according to claim 1, characterized in that: d1≥50nm; and / or, d3≤1500nm; and / or, the lithium iron phosphate further includes fourth particles with a particle size of d4, d4≥2μm.

3. The positive electrode sheet according to claim 2, characterized in that: In an area of ​​50 μm×50 μm on the surface of the active material layer, based on the total number of all lithium iron phosphate particles, the number of the first particles accounts for 35%-40%; and / or, The amount of the second particles accounts for 60%-64%; and / or, The amount of the third particles accounts for 0.5%-1%; and / or, The quantity of the fourth particles accounts for less than 0.1%.

4. The positive electrode sheet according to claim 2, characterized in that: The first particles, the second particles and the third particles are primary particles, and the fourth particles are secondary particles formed by agglomeration of the first particles.

5. The positive electrode sheet according to claim 1, characterized in that: The active material includes a lithium supplement; the lithium supplement includes at least one of a ternary lithium compound and a binary lithium compound.

6. The positive electrode sheet according to claim 5, characterized in that: The mass ratio a of the first particles to the lithium supplement agent satisfies 1≤a≤10; And / or, the ternary lithium compound is Li5FeO4.

7. The positive electrode sheet according to any one of claim 5, characterized in that: The raw materials of lithium iron phosphate in the active material include first lithium iron phosphate and second lithium iron phosphate; the first particles come from the first lithium iron phosphate, and the second particles and the third particles come from the second lithium iron phosphate.

8. The positive electrode sheet according to claim 7, characterized in that: Based on the total mass of the active material, the mass content W1 of the first lithium iron phosphate satisfies: 0<W1<40wt%; the mass content W2 of the second lithium iron phosphate satisfies: 60wt%≤W2<100wt%, and the mass content W3 of the lithium supplement agent satisfies: W3<5wt%; and / or, The particle size distribution curve of the first lithium iron phosphate is a bimodal curve, the high peak particle size of the bimodal curve is the first peak particle size, and the low peak particle size is the second peak particle size; the first peak particle size is higher than 10 μm, and the second peak particle size is not higher than 1 μm; and / or, The particle size distribution curve of the second lithium iron phosphate is a bimodal curve, the high peak particle size of the bimodal curve is the third peak particle size, and the low peak is the fourth peak particle size; the third peak particle size is not higher than 1 μm, and the fourth peak particle size is 1 μm-10 μm.

9. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The mass content of active material in the active material layer is 85-98wt%; and / or, The surface density of the positive electrode sheet is 15-28 mg / cm 2 and / or, The compaction density of the positive electrode sheet is 2.0-2.7 g / cm 3 and / or, The surface resistance of the positive electrode plate is 200-500 mΩ; and / or, The thickness of the positive electrode plate is 120-205 μm.

10. A battery, characterized in that: The invention comprises the positive electrode sheet as described in any one of claims 1 to 9.